Green synthesis of dimethyl isosorbide - Tundo, Pietro (2010)
A green synthetic approach for dimethyl isosorbide (DMI) with dimethylcarbonate (DMC) in the presence of a base is reported. The easy methylation of isosorbide may be due to its unique structure (which enhances the nucleophilicity of the hydroxyl groups), and to the effect of the hydrogen bonding which increases the reactivity of the molecule towards DMC.